2014
DOI: 10.1021/jf5017175
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of Chlorantraniliprole and Cyantraniliprole in Water and Soil: Verification of Degradation Pathways via Kinetics Modeling

Abstract: Photodegradation of [(14)C]-chlorantraniliprole (CLAP) and [(14)C]-cyantraniliprole (CNAP) was investigated in sterile buffer solutions, in natural water, and on soil surfaces. Both compounds displayed rapid degradation in aqueous buffers when exposed to light at concentrations which could result from direct overspray to a shallow water body. While the main products observed had analogous structures, a substantial difference was noted in the rate of degradation of the two compounds despite minimal differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 11 publications
3
16
0
Order By: Relevance
“…The current study confirmed that the soil treatments that non-sterilized showed higher dissipation than serialized soil. This finding is in agreement with previous studies which found that the non-sterilized soil had high dissipation of CAP compared to the sterilized soil (Fletcher and Kaufman 1980;Sharma et al 2014a). The factor of soil amendment in the present study confirmed that the soil-wheat straw showed higher dissipation that soil of non-wheat straw.…”
Section: Figure 3 Dissipation Curves Of Cap In Soil a And B With Or supporting
confidence: 93%
“…The current study confirmed that the soil treatments that non-sterilized showed higher dissipation than serialized soil. This finding is in agreement with previous studies which found that the non-sterilized soil had high dissipation of CAP compared to the sterilized soil (Fletcher and Kaufman 1980;Sharma et al 2014a). The factor of soil amendment in the present study confirmed that the soil-wheat straw showed higher dissipation that soil of non-wheat straw.…”
Section: Figure 3 Dissipation Curves Of Cap In Soil a And B With Or supporting
confidence: 93%
“…In addition, the DBE data and MS 2 experiments, conducted through the selection of the ions m/z 244 [M+HÀCl] + and 209 [M + HÀCl 2 ] + , are also consistent with the proposed structure MET 7. This transformation product was also identified by Sharma et al [42], although other intermediates detected by some authors in recent studies related to hydrolysis, and chemical and photochemical degradation of CL [37,42,43] were not recovered in our case. Fig.…”
Section: Identification and Evolution Of The Photo-transformation Prosupporting
confidence: 78%
“…On the other hand, only a 20% reduction in its concentration was obtained after 60 min of light exposure in the absence of a catalyst (photolytic test). Recently, some authors have noted that photolysis of CL in pH 7 buffer proceeds rapidly with the time needed for disappearance of 50% of the compound (DT 50 ) lower than one day and the constituents of natural water can alter the process, increasing the degradation rate [37].…”
Section: Evolution Of Chlorantraniliprole Residuesmentioning
confidence: 99%
“…Two of the major difficulties in such studies are: (1) being able to recover a non-target compound from the matrix and (2) correlating the decrease in the signal of the precursor pollutant with the presence of new features in LC-MS chromatograms. An effective, although expensive and not always possible, solution to the above problem is to label the precursor species with a nonstable, radioactive isotope [1,2]. Another possibility is to divide the study in two steps.…”
Section: Introductionmentioning
confidence: 99%